A network perspective on the relationship between gaming disorder, depression, alexithymia, boredom, and loneliness among a sample of Chinese university students. (November 2021) - Li, Li; Niu, Zhimin; Griffiths, Mark D.; Wang, Wen; Chang, Chunying; Mei, Songli
Abstract: Background and aims: Based on previous research, it was hypothesized that negative affect (e.g., depression, anxiety, and loneliness) and low level of emotion regulation (i.e., alexithymia) are risk factors for internet gaming disorder (IGD). Research utilizing a network analysis approach to psychopathology has increased rapidly, and is used to examine the pattern of interactions between causal factors of mental health disorders. Previous research has investigated the relationship between gaming disorder (GD), depression, alexithymia, boredom, and loneliness by pair-wise correlation and correlation of three or four variables. However, to date, network analysis has rarely been utilized to examine the relationship between the aforementioned multi-variables. Therefore, the present study used network analysis to examine the relationship between GD, depression, alexithymia, boredom, and loneliness among a sample of Chinese university students. Methods: A sample comprising 1635 Chinese university students (913 males) completed a survey including the Gaming Disorder Test, Patient Health Questionnaire, and Toronto Alexithymia Scale, alongside single-item measures of loneliness and boredom. Results: Depression, alexithymia, boredom, and loneliness were significantly and positively associated with GD. Loneliness and boredom had the closest edge intensity, and loneliness was the strongest central node in the domain-level network. The facet-level and the item-level network analysis also showed that GD was connected with depression, alexithymia, boredom, and loneliness. The domain-level network comparison test (NCT) showed the global strengths had significant difference among gender group (males = 1.90 vs. females = 1.77, p  = 0.013). Conclusions: The findings indicate that there is a close relationship between GD, depression, alexithymia, boredom, and loneliness. Negative affect and low emotion regulation may induce or worsen GD, resulting in a vicious cycle. Practitioners developing interventions to overcome GD should consider aspects aimed at adjusting and improving negative emotion, especially loneliness and related negative affect as well as facilitating positive emotion. Highlights: Loneliness and boredom had the closest edge intensity in domain-level network. Loneliness was the strongest central node in domain-level network. There is a close relationship between GD, depression, alexithymia, boredom, and loneliness. There were significant differences in the global edge strength between gender groups among Chinese university students.